Experiences shaping research career intention among Black, Hispanic, and Indigenous-identifying first-year allopathic medical students in the United States: A qualitative study - Shruthi Venkataraman; Meghan O’Connell; Adeola Ayedun; Allison Aviles; Alexandra M. Hajduk; Mytien Nguyen; Gbenga Ogedegbe; Laura Castillo-Page; David Henderson; Judee Richardson; Leslie A. Curry; John Paul Sánchez; et al. (PLoS ONE, 2026)
Objective To examine the early experiences influencing research career intentions (RCI) among MD students from racial and ethnic backgrounds underrepresented in medicine (URiM). Methods We conducted semi-structured, in-depth interviews with 31 first-year URiM medical students from MD-granting programs across the US to examine student-reported experiences influencing RCI. Results Participants were first-year medical students (N = 31; mean age 24.8 ± 2.6 years; 64.5% female) identifying as Black (38.7%), Hispanic (32.3%), or Multiracial (29%). Four themes were identified: (1) structured premedical research exposure was described as pivotal to developing early research engagement and interest in research careers; (2) research orientations reflected a commitment to using research as a vehicle for social justice and community impact; (3) high-quality research mentorship was characterized by authentic relational investment, skill development, and the distinct value of racial and ethnic identity-concordant role models; and (4) the research arms race for residency placement was described as amplifying systemic inequities that constrained students’ research engagement. Across themes, students described tensions between academic research culture and their personal values, including a desire to advance equity and contribute meaningfully to science. For some, this misalignment made research feel less purposeful or personally aligned. Conclusions Medical training programs seeking to support URiM students’ RCI should invest in structured premedical research programs and expand access to research mentorship that is both relationally invested and identity concordant. Efforts to cultivate sustained engagement should address publication pressures tied to residency competitiveness, which amplify structural barriers and misalign with students’ motivations for pursuing research. Broadening definitions of scholarly contribution and fostering research environments that affirm students’ values may be critical to building a robust physician-scientist workforce.